CD4+ T cells targeting dominant and cryptic epitopes from Bacillus anthracis Lethal Factor - Stephanie eAscough; Rebecca Jo Ingram; Karen eChu; Julie eMusson; Stephen eMoore; Theresa eGallagher; Leslie eBaillie; Ethel Diane Williamson; John eRobinson; Bernard eMaillere; Rosemary eBoyton; Daniel eAltmann (Frontiers in Microbiology, 2016)
Anthrax is an endemic infection in many countries, particularly in the developing world. The causative agent, Bacillus anthracis, mediates disease through the secretion of binary exotoxins. Until recently, research into adaptive immunity targeting this bacterial pathogen has largely focused on the humoral response to these toxins. There is, however, growing recognition that cellular immune responses involving IFNγ producing CD4+ T cells also contribute significantly to a protective memory response. An established concept in adaptive immunity to infection is that during infection of host cells, new microbial epitopes may be revealed, leading to immune recognition of so called ‘cryptic’ or ‘subdominant’ epitopes. We analysed the response to both cryptic and immunodominant T cell epitopes derived from the toxin component lethal factor and presented by a range of HLA-DR alleles. Using IFNγ-ELISPOT assays we characterised epitopes that elicited a response following immunisation with synthetic peptide and the whole protein and tested their capacities to bind purified HLA-DR molecules in vitro. We found that DR1 transgenics demonstrated T cell responses to a greater number of domain III cryptic epitopes than other HLA-DR transgenics, and that this pattern was repeated with the immunodominant epitopes, a greater proportion of these epitopes induced a T cell response when presented within the context of the whole protein. Immunodominant epitopes LF457-476 and LF467-487 were found to induce a T cell response to the peptide, as well as to the whole native LF protein in DR1 and DR15, but not in DR4 trangenics. The analysis of Domain I revealed the presence of several unique cryptic epitopes all of which showed a strong to moderate relative binding affinity to HLA-DR4 molecules. However, none of the cryptic epitopes from either domain III or I displayed notably high binding affinities across all HLA-DR alleles assayed. These responses were influenced by the specific HLA alleles presenting the peptide, and imply that construction of future epitope string vaccines which are immunogenic across a wide range of HLA alleles could benefit from a combination of both cryptic and immunodominant anthrax epitopes.